USING THE LEGO CONSTRUCTION KITS IN PRESCHOOL EDUCATION - HAVELKA, Martin; CASTKOVA, Pavlina (Trends in education, 2015)
This paper deals with the problems of using the Lego construction kits in kindergartens emphasizing development of cognitive processes and thinking of children through playing and games. This paper introduces partial results of Lego construction kits analysis; based on that two selected sets are specified in more details and possible ways of using them in technical education at kindergartens are outlined.
Keywords: preschool education; preschool child; polytechnic education; LEGO Duplo construction kits; development of cognitive processes and thinking of preschool children.